2016
DOI: 10.1111/pde.13050
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Survey of Stevens–Johnson Syndrome and Toxic Epidermal Necrolysis in Children in the United States

Abstract: Although Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are serious, life-threatening reactions to drug therapies, no efforts have been made to investigate the comprehensive change in epidemiology with respect to age, sex, and race and ethnicity in children. The risk of death was 0.3% to 1.5%, and the highest hospitalization rates were in children 15 to 19 years of age, boys, and black children. The highest proportions of hospitalizations were children with very low household income, those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Large, metropolitan hospitals may treat more complicated cases of SJS–TEN leading to higher readmission rates. Previous studies found increased hospitalization for SJS–TEN in children admitted to large, metropolitan teaching hospitals …”
Section: All‐cause Readmission Rates For Stevens–johnson Syndrome (Sjmentioning
confidence: 94%
See 2 more Smart Citations
“…Large, metropolitan hospitals may treat more complicated cases of SJS–TEN leading to higher readmission rates. Previous studies found increased hospitalization for SJS–TEN in children admitted to large, metropolitan teaching hospitals …”
Section: All‐cause Readmission Rates For Stevens–johnson Syndrome (Sjmentioning
confidence: 94%
“…Previous studies found increased hospitalization for SJS-TEN in children admitted to large, metropolitan teaching hospitals. 5 Together, these findings suggest the high occurrence of readmission among inpatients with SJS-TEN is secondary to both disease-specific sequelae and systemic comorbidities. Close follow-up care after hospital discharge may help prevent readmission.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…person-years which is higher than adults in some nationwide studies. [30][31][32][33][34] Despite an increased frequency of HRs to AEDs in childhood, recent studies showed that the risk of death with SJS/TEN is lower in children than in adults. 14,30,32,34 Given the above knowledge, the concomitant administration of AEDs should always be undertaken with caution and using a slower titration.…”
Section: Key Messagementioning
confidence: 99%
“…In addition, children who used a single AED had a lower frequency of HRs than those who used multiple AEDs; 3.8% vs 4.4%, respectively 5 . Moreover, the overall incidence rate of SJS/TEN among children was reported to be 5 to 7 cases per million person‐years which is higher than adults in some nationwide studies 30‐34 . Despite an increased frequency of HRs to AEDs in childhood, recent studies showed that the risk of death with SJS/TEN is lower in children than in adults 14,30,32,34 …”
Section: Immune Pathomechanisms Risk Factors and Geneticsmentioning
confidence: 99%